(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Chronic hepatitis (CH) represents a significant epidemiological challenge in the global healthcare system, with its development influenced by a complex interplay of metabolic, viral, and socio-hygienic factors. In recent years, dietotherapy has been increasingly recognized as an essential component of the comprehensive management of patients with CH. The objective of this literature review is to analyze the clinical effectiveness of dietotherapy in chronic hepatitis based on contemporary scientific evidence. According to the analyzed data, balanced nutrition—particularly diets rich in antioxidants, characterized by a low glycemic index, and containing hepatoprotective components—has been shown to reduce liver enzyme levels (ALT, AST), attenuate inflammatory processes, and slow the progression of fibrosis. Conversely, high-calorie and high-fat diets contribute to accelerated disease progression. When combined with pharmacotherapy, dietotherapy significantly improves clinical outcomes.